Designing an Innovative Digital Learning Material for Arabic Vocabulary in Madrasah Tsanawiyyah - Ramadhan, Gilang; Rahmawati, Rahmawati; Hadi, Syofyan; Gustian, Nabil (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2025)
This study aims to design an innovative Arabic–Indonesian thematic digital dictionary tailored to the pedagogical needs of Madrasah Tsanawiyah (MTs) students. Existing digital dictionaries, such as Google Translate and Al-Ma’any, function mainly as general translation tools and do not align with curriculum requirements. Using a descriptive qualitative approach, this research involved needs analysis, conceptual design, and expert validation. Findings show a very high need for thematic digital vocabulary tools among students (85.83%) and teachers (90.91%). The proposed Q.S Dictionary integrates two core features: a Word Search feature for independent and efficient access to meanings, and a Word Example feature to support contextual understanding. UI/UX design was prioritised to enhance learners’ motivation and engagement. Expert validation results indicated high feasibility, with 91.67% from material experts and 97.5% from IT experts. The study provides a validated conceptual framework for developing pedagogically aligned digital vocabulary materials for MTs students.